2018
DOI: 10.11152/mu-1084
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of the fetal common arterial trunk. A case series

Abstract: Fetal common arterial trunk is an anomaly represented by a unique arterial trunk that arouses from the base of the heart, and gives birth to systemic branches, both pulmonary and coronary, frequently associated with a ventricular septal defect (VSD) and has a poor prognosis. We present a series of 17 cases diagnosed in our tertiary center with different types of fetal common arterial trunk, its associated disorders, the evolution of the pregnancies, and of the neonates. We concluded that our cases support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Fetal malformations present multidisciplinary involvements regarding the diagnosis, the therapeutic approach and the prognosis [18][19][20][21][22][23][24][25][26][27][28]. Therefore, prenatal diagnosis is the cornerstone factor that can influence the prognosis of these fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal malformations present multidisciplinary involvements regarding the diagnosis, the therapeutic approach and the prognosis [18][19][20][21][22][23][24][25][26][27][28]. Therefore, prenatal diagnosis is the cornerstone factor that can influence the prognosis of these fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, among which, only 12 had a gestational age lower than 24 weeks. They reported that among them, 9 cases had type 1, 2 cases had type 2, and in 6 cases, they could not establish a well-defined type (11).…”
Section: Discussionmentioning
confidence: 99%
“…The other genetic syndromes, indexed in the genesis of this cardiac anomaly are as follows: Ivemark syndrome, Fryns syndrome, Carpentier syndrome, Ellis Van Creveld syndrome, Cornelia De Lange syndrome, and Meckel-Gruber syndrome (13). Trisomies 21, 18, or 13 can be observed in 4.5% of the cases (14, 15); even the rare trisomy 8 is also detected in some cases (16,17 (19). Some maternal factors involved in truncus arteriosus include the following: infections in utero, like maternal rubella; metabolic disorders, like maternal diabetes mellitus type 1 and 2; chronic maternal disease; hypertension, and obesity (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is a noninvasive, fast, and widely available imaging method, with remarkable developments lately in terms of myocardial deformation, 3D echocardiography, and also intrauterine diagnosis. 11,12 Regarding orthotopic heart transplantation, some authors suggested that LV mass increases and tissue Doppler indices decrease during rejection episodes. [13][14][15] Serial myocardial perfusion imaging (MPI) measurements can be used for the detection of rejection.…”
Section: Discussionmentioning
confidence: 99%